2012
DOI: 10.1371/journal.pone.0037484
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric Spawning but Allopatric Distribution of Anguilla japonica and Anguilla marmorata: Temperature- and Oceanic Current-Dependent Sieving

Abstract: Anguilla japonica and Anguilla marmorata share overlapping spawning sites, similar drifting routes, and comparable larval durations. However, they exhibit allopatric geographical distributions in East Asia. To clarify this ecological discrepancy, glass eels from estuaries in Taiwan, the Philippines, Indonesia, and China were collected monthly, and the survival rate of A. marmorata under varying water salinities and temperatures was examined. The composition ratio of these 2 eel species showed a significant lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
(85 reference statements)
0
20
0
Order By: Relevance
“…5B). No small A. marmorata leptocephali have been collected in the Indonesian Seas (Aoyama et al 2003), which, along with the findings of population structure studies (Minegishi et al 2008), indicates that the larvae of the North Pacific population disperse widely to regions along the western and southern margins of the western North Pacific after spawning in the NEC Han et al 2012a;Leander et al 2013).…”
Section: Distribution and Dispersal Of Anguillid Larvaementioning
confidence: 85%
See 1 more Smart Citation
“…5B). No small A. marmorata leptocephali have been collected in the Indonesian Seas (Aoyama et al 2003), which, along with the findings of population structure studies (Minegishi et al 2008), indicates that the larvae of the North Pacific population disperse widely to regions along the western and southern margins of the western North Pacific after spawning in the NEC Han et al 2012a;Leander et al 2013).…”
Section: Distribution and Dispersal Of Anguillid Larvaementioning
confidence: 85%
“…1). These Northern Hemisphere anguillid eels are temperate species, but the North Pacific population of the giant mottled eel (Anguilla marmorata), a tropical species, also spawns offshore in the NEC in an overlapping area with A. japonica, and its leptocephali disperse even more widely Han et al 2012a;Leander et al 2013). The newly discovered species the Luzon eel (Anguilla luzonensis) may also spawn in the same area (Kuroki et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Why A. japonica larvae only enter the KC region, while A. marmorata, after being transported by the NEC, can enter both the northwardly flowing KC (which carries them to eastern China, southern Japan, and Korea) and the southwardly flowing Mindanao Current (that carries them to recruitment areas in northern Indonesia, the Philippines, and Taiwan), is still unclear (Kuroki et al ×2009). Recently, Han et al (2012) pointed out that recruitment temperature preferences and oceanic current systems control the distinct biogeography of A. japonica and A. marmorata. Aside from these abiotic parameters, biological factors should also be taken into consideration in explaining this ecological discrepancy, but the early life histories of these two species particularly during the oceanic phase are not yet fully understood, especially that of A. marmorata.…”
Section: Introductionmentioning
confidence: 99%
“…Upon reaching continental waters, it was also found that their distributions in estuaries also geographically differed. For example, A. japonica is abundant along the northern and western coasts of Taiwan, while A. marmorata is abundant along the southern and eastern coasts (Leander et al 2012;Han et al 2012). In addition, it was also observed that in the same river system, A. marmorata occupied the upper reaches while A. japonica occupied the lower reaches (Shiao et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…2014 (A. rostrata), (A. bicolor bicolor or bicolor pacifica A. marmorata) (A. mozambica) . (Daverat et al, 2006;Leander et al, 2012), (Wouthuyzen et al, 2009;Han et al, 2012), (Gagnaire et al, 2011), (Luo et al, 2013) , . A. rostrata, A. bicolor pacifica A. marmorata A. japonica .…”
Section: Rostrata)mentioning
confidence: 99%